Analisis Implementasi Standar Proses Pembelajaran pada SD Negeri 6 Kediri - Ni Luh Made Ari Krisna Yanti; A.A. Sagung Dewi Cahya Ningrat; Ni Wayan Ratih (Metta : Jurnal Ilmu Multidisiplin, 2026)
The implementation of learning process standards is an essential aspect of improving the quality of primary education in accordance with the National Education Standards. This study aims to analyze the implementation of learning process standards at SD Negeri 6 Kediri, covering the aspects of lesson planning, instructional implementation, assessment, and learning supervision. The study employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and document analysis involving the principal, classroom teachers, and educational staff. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of learning process standards at SD Negeri 6 Kediri has generally been carried out effectively in accordance with the applicable curriculum. Teachers have developed instructional plans that accommodate students’ characteristics and have implemented active, interactive, and student-centered learning practices. Assessment has been conducted through both formative and summative assessments, while learning supervision has been carried out through regular academic supervision by the principal. Nevertheless, several aspects still require improvement, particularly the utilization of assessment results as a basis for instructional follow-up, the implementation of reflective evaluation practices, teachers’ digital competencies, and the availability of digital learning facilities. This study contributes to the understanding that the successful implementation of learning process standards is determined not only by effective planning and instructional delivery but also by the optimization of assessment follow-up, the strengthening of reflective evaluation practices, and adequate digital resources in primary schools.